2020
DOI: 10.1038/s41598-020-69558-y
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of laminin-511 in the basement membrane due to photoaging reduces epidermal stem/progenitor cells

Abstract: Daily sunlight exposure damages the epidermal basement membrane (BM) and disrupts epidermal homeostasis. inter-follicular epidermal stem cells (ife-Scs) regulate epidermal proliferation and differentiation, which supports epidermal homeostasis. Here, we examine how photoaging affects the function of ife-Scs and we identify key components in their cellular environment (niche). We found that sun-exposed skin showed a decrease of MCSP-positive and β1-integrin-positive cells concomitantly with a decrease of lamini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 56 publications
1
33
0
Order By: Relevance
“…Laminin staining was also predominantly basal but was more convoluted in appearance with some inter-digitation with the epidermis as compared to collagen IV (Additional file 2: Fig S2D). We also note with interest that such inter-digitation has been observed in other human skin sections [33] and cornea [34]. It is also notable that other ECM ligands may play a role in this context, including collagen XXIII that has been shown to be a ligand for α2β1 and localises to cell-cell adhesions in the human skin [35].…”
Section: Results and Discussion α2β1 Integrins Contribute To Cell-cell Adhesion Assemblysupporting
confidence: 55%
“…Laminin staining was also predominantly basal but was more convoluted in appearance with some inter-digitation with the epidermis as compared to collagen IV (Additional file 2: Fig S2D). We also note with interest that such inter-digitation has been observed in other human skin sections [33] and cornea [34]. It is also notable that other ECM ligands may play a role in this context, including collagen XXIII that has been shown to be a ligand for α2β1 and localises to cell-cell adhesions in the human skin [35].…”
Section: Results and Discussion α2β1 Integrins Contribute To Cell-cell Adhesion Assemblysupporting
confidence: 55%
“…We previously developed HEI as a bi-functional inhibitor of both MMP-9 and heparinase. Topical application of HEI promoted reconstruction of the basememt membrane and deposition of laminin-511 by inhibiting the activities of MMP-9 and heparinase in an organotypic human skin model 11 , thereby maintaining MCSP-positive epidermal stem cells and promoting epidermal homeostasis and barrier recovery 10,11 . Dermal regeneration of facial skin was also promoted by treatment with HEI, improving the elasticity of the papillary dermis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…6B). We previously reported that epidermal stem cell levels were maintained by blocking the degradation of laminin-511 mediated by MMP-9 and heparinase 10 . Thus, we next investigated the effect of laminin-511 on cytokine secretion.…”
Section: Pdgfb Expression In Keratinocytes Was Reduced In An Age-dependent Manner and Was Affected By The Basement Membrane Conditionmentioning
confidence: 99%
See 2 more Smart Citations